Anatomizing Civil War Studies in Lucan's Epic Technique - Dinter, Martin T. (University of Michigan Press, 2013)
Imperial Latin epic has seen a renaissance of scholarly interest. This book illuminates the work of the poet Lucan, a contemporary of the emperor Nero who as nephew of the imperial adviser Seneca moved in the upper echelons of Neronian society. This young and maverick poet, whom Nero commanded to commit suicide at the age of 26, left an epic poem on the civil war between Caesar and Pompey that epitomizes the exuberance and stylistic experimentation of Neronian culture. This study focuses on Lucan's epic technique and traces his influence through the Middle Ages and the Renaissance.Martin T. Dinter's newest volume engages with Lucan's use of body imagery, sententiae, Fama (rumor), and open-endedness throughout his civil war epic. Although Lucan's Bellum Civile is frequently decried as a fragmented as well as fragmentary epic, this study demonstrates how Lucan uses devices other than teleology and cohesive narrative structure to bind together the many parts of his epic body.